STUDENTS’ RESPONSES TOWARD THE IMPLEMENTATION OF BINGO GAME WITH SCIENTIFIC APPROACH IN TEACHING WRITING DESCRIPTIVE TEXT (IKIP Siliwangi, 2021)
This study aimed to investigate the implementation of the Bingo game technique in teaching writing and to find out the students’ participation toward the implementation of the Bingo game. The research instruments used interview and observation sheet. This study was conducted at Junior High School in Cimahi. The students of VII F class were selected as the participant of the research. The research used descriptive qualitative method. The data was obtained from classroom observation and students’ interview. The result showed that Bingo game can be used to motivate students in writing skill. It was very helpful in providing the students with more enjoyable activities which made the students involved in the teaching and learning process actively. Keywords: Writing, Bingo Game, Descriptive Text.